THE MEANING AND CONTENT OF THE MODERNIZING PROCESSES OF PEDAGOGY IN THE UNIVERSITIES - Malgazhdarova T.G., (Academic Journal of Physical and Chemical Sciences, 2020)
Higher school pedagogy is based on the pedagogical science. This is the science of the pedagogical laws, the essence, principles, methods and forms of education, upbringing, development and professional training of the particular person, team with the interests of the successful activity. The emergence of higher school pedagogy is associated with the first associations of the people for joint life activity; in order to implement it, appropriate training was conducted. As an independent branch, pedagogy was formed only after the accumulation of the general and special pedagogical knowledge. Pedagogy reveals the most stable and significant relationships, dependencies between training, education, development and comprehensive training of the people and social groups. Studying the pedagogical aspects of the process of education (self-education), training, development, self-development and professional training of the people for the certain type of activity, higher school pedagogy substantiates the principles, methods and organizational forms of the educational work, recommendations, rules, management techniques, etc. Higher school pedagogy is a branch of the pedagogical science, which studies the pedagogical laws and means of organizing and implementing the higher educational process.